The potential effects of chlorophyll-deficient mutation and tree_age on the accumulation of amino acid components in tea plants. (15th June 2023) - Liu, Dingding; Wei, Kang; Zhang, Chenyu; Liu, Haoran; Gong, Yang; Ye, Yuanyuan; Chen, Jiedan; Yao, Mingzhe; Chen, Liang; Ma, Chunlei
Highlights: A large-scale samples and multi-year, multi-point data was used to characterize the variation of amino acids in tea plant. The potential effects of tree age on the accumulation of amino acid components in tea plants was investigated in two hybrid populations. The accumulation of amino acids in tea plant was closely related to leaf color variation and the tree age during growing period. Abstract: Albino tea has been receiving growing attention on the tea market due to its attractive appearance and fresh taste, mainly caused by high amino acid contents. Here, variations in the contents of five free amino acids in relation to pigment contents and tree age in two hybrid populations'Longjin 43′(♀) × 'Baijiguan'(♂) and 'Longjin 43′(♀) ×'Huangjinya'(♂) with 334 first filial generation individuals including chlorophyll-deficient and normal tea plants were investigated. The data showed that the contents of main amino acids in all filial generation gradually decreased as plant age increased. Principal component analysis indicated that the amino acid content of individual plant tended to be stable with the growth of plants. Correlation analysis clarified that several main amino acids were significantly negatively correlated with chlorophyll a, chlorophyll b and carotenoid contents. Our results showed that the accumulation of amino acids in tea plant was closely related to leaf color variation and the tree age during growing period.